Bans, tests and alchemy: Food safety standards and the Ugandan fish export industry - Stefano Ponte (Danish Institute for International Studies (DIIS), 2005)
Fish exports are the second largest foreign exchange earner in Uganda. When Uganda's fish export industry started to operate in the late 1980s and early 1990s, one may have thought that fish was being turned into gold. From an export value of just over one million US in 1990, the mighty Nile Perch had earned the country over 45 million US just six years later. But alchemy proved to be more than the quest of the philosophers' stone to change base metals into gold. From 1997 to 2000, the industry experienced a series of import bans, imposed by the EU on grounds of food safety. Despite claims to the contrary, the EU did not provide scientific proof that fish was actually `unsafe'. Rather, the poor performance of Uganda's regulatory and monitoring system was used as a justification. The `system', as the characters of an allegory, has no individual personality and is the embodiment of the moral qualities that `the consumer' expects from `responsible operators' in the fish sector. Only by fixing this system of regulations and inspections, and by performing the ritual of laboratory testing did the Ugandan industry regain ist status as a `safe' source of fish. Fish exports now earn almost 90 million US to the country. This apparent success story was achieved by a common front comprising government authorities and the processing industry, a high level of private-public collaboration not often seen in East Africa. Yet, important chunks of the regulatory and monitoring system exist only on paper. Furthermore, the system is supposed to achieve a series of contradictory objectives: to facilitate efficient logistics and ensure food safety; to match market demand and take care of sustainability; to implement a top-down food safety monitoring system and a bottom-up fisheries co-management system. This means that at least some food safety-related operations have to be carried out as `rituals of verification'. Given the importance of microbiological tests and laboratories in the food safety compliance system, alchemic rituals are perhaps a more appropriate metaphor. While the white coats and advanced machinery of present-day alchemists reassure insecure European regulators and consumers, it leaves the Ugandan fish industry in a vulnerable position. In Uganda, fish can now be turned into gold again – but for how long?
Keywords: 330; Fischerei; Fischindustrie; Exportindustrie; Lebensmittelüberwachung; Normung; Uganda; Victoriasee